Available power and wind variability typical case of the Pimentel district - Pérez S., José C. (2017)
The present work begins by describing the meteorological variables of a wind farm. Subsequently, the equations defining Betz's law and the Weibull distribution are analyzed, in order to understand the amount of power and time of operation available from a wind turbine, as well as the load factor of a wind farm. Finally, the influence of surface roughness on wind variation and the selection of a proper location are discussed.